Animals in Greek and Roman Religion and Myth - Johnston, Patricia A. (Cambridge Scholars Publishing, 2016)
This volume brings together a variety of approaches to the different ways in which the role of animals was understood in ancient Greco-Roman myth and religion, across a period of several centuries, from Preclassical Greece to Late Antique Rome. Animals in Greco-Roman antiquity were thought to be intermediaries between men and gods, and they played a pivotal role in sacrificial rituals and divination, the foundations of pagan religion. The studies in the first part of the volume examine the role of the animals in sacrifice and divination. The second part explores the similarities between animals, on the one hand, and men and gods, on the other. Indeed, in antiquity, the behaviour of several animals was perceived to mirror human behaviour, while the selection of the various animals as sacrificial victims to specific deities often was determined on account of some peculiar habit that echoed a special attribute of the particular deity. The last part of this volume is devoted to the study of animal metamorphosis, and to this end a number of myths that associate various animals with transformation are examined from a variety of perspectives